2003
DOI: 10.1016/s0161-6420(03)00493-7
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography assessment of retinal nerve fiber layer thickness changes after glaucoma surgery

Abstract: Purpose-To assess changes in retinal nerve fiber layer (NFL) thickness in glaucoma patients after filtration surgery by using optical coherence tomography (OCT). Design-Retrospective observational case series.Participants-Thirty-eight eyes of 31 glaucoma patients who underwent trabeculectomy or a combined procedure of cataract extraction and trabeculectomy were evaluated retrospectively.Methods-Eyes were imaged with OCT before surgery (1 week to 6 months before surgery; mean ± standard deviation [SD], 71.3 ± 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
3
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 25 publications
4
77
3
6
Order By: Relevance
“…Recent studies suggest that the variations in RNFL thickness are correlated with variations in IOP, that is, for each reduction of 1 mmHg in IOP, there is an increase in RNFL of 0.5 mm. 42 These data are, however, much debated since, although they are confirmed by some experimental studies, 43,44 frequently in single sectors, 45 in others no optic nerve modifications related to pressure variations have been found. 46,47 It is still not clear what causes an improvement in the RNFL following a reduction in IOP.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies suggest that the variations in RNFL thickness are correlated with variations in IOP, that is, for each reduction of 1 mmHg in IOP, there is an increase in RNFL of 0.5 mm. 42 These data are, however, much debated since, although they are confirmed by some experimental studies, 43,44 frequently in single sectors, 45 in others no optic nerve modifications related to pressure variations have been found. 46,47 It is still not clear what causes an improvement in the RNFL following a reduction in IOP.…”
Section: Discussionmentioning
confidence: 96%
“…16 A major increase in the retinal nerve fibre thickness (Po0.0001) was found as the IOP decreased from 22.0 to 11.4 mmHg. Although the exact pathomechanism is not known, it is assumed that the lamina cribrosa moves forward as the consequence of decrease of the IOP and so the nerve fibre layer may regain its original shape and thickness, until the glaucomatous changes are not irreversible.…”
Section: Eyementioning
confidence: 91%
“…Previous studies have reported that cataract surgery results in an increase in measured RNFL retardance and thus SLP-measured RNFLT. [21][22][23] Reports on the systematic differences of measured RNFLT pre-and post trabeculectomy are conflicting for OCT, 24,25 and have been shown not to be significant for SLP. 26 In light of these findings, data from eyes with glaucoma surgery during follow-up were analysed, whereas those from eyes with cataract surgery were not.…”
Section: Participantsmentioning
confidence: 99%